PengaruhTepung Kelordan Katuk dalam Ransum terhadap Kecernaan Serat Kasar, Lemak KasarTernak Babi: The Effect of Moringa Flour and Katuk in the Ration on Digestibility of Crude Fiber, Crude Fat of Pigs - Yohanes Paulus Juan Bagus Pampo; Sabarta Sembiring; Ni Nengah Suryani (Jurnal Peternakan Lahan Kering, 2024)
The purpose of this study was to determine the effect of a mixture of Moringa leaf flour andsauropus leaf meal in the basal diet on the consumption and digestibility of crude fiber and crudefat of grower landrace crossbreed pigs. The material used was 12 castration male pigs aged 2-3months with an average initial body weight of 29.83 kg with a coefficient of variance 18.16%. Thedesign used was a Randomized Block Design with 4 treatments and 3 replications. The treatmentstested were R0: 100% basal died (control), R1: 95% basal died + 5% mixture of moringa andsauropus leaf meal, R2: 90% basal died + 10% mixture of moringa and sauropus leaf meal, R3:85% basal died + 15% mixture of moringa and katuk leaf meal. The ratio of the mixture ofMoringa leaf flour and katuk leaf flour is 4:1. Variables evaluated in the study were: intake anddigestibility of crude fiber and crude fat. The results of the analysis of variance ANOVA thetreatment had no significant effect (P>0.05) on the consumption and digestibility of crude fiberand crude fat. It can be concluded that the use of a mixture of Moringa leaf flour and katuk leafflour up to 15% in the ration has the same effect on consumption and digestibility of crude fiberand crude fat in grower phase pigs. Tujuan penelitian adalah untuk mengetahui pengaruh campuran tepung daun kelor (Moringaoleifera) dan tepung daun katuk (Sauropus androgynus L. Merr) dalam ransum basal terhadapkonsumsi dan kecernaan serat kasar dan lemak kasar ternak babi peranakan landrace fase grower.Materi yang digunakan adalah 12 ekor ternak babi jantan kastrasi berumur 2-3 bulan dengan rata-rata bobot badan awal 29,83Kg dengan Koefisien varians 18,16%. Rancangan yang digunakanadalah Rancangan Acak Kelompok dengan 4 perlakuan dan 3 ulangan. Perlakuan yang dicobakanadalah R0: 100% ransum basal (control), R1: 95% ransum basal + 5% campuran tepung daunkelor dan katuk, R2: 90% ransum basal + 10% campuran tepung daun kelor dan tepung daunkatuk, R3: 85% ransum basal + 15% campuran tepung daun kelor dan tepung daun katuk.Perbandingan campuran tepung daun kelor dan tepung daun katuk adalah 4:1.Variabel yang ditelitiadalah konsumsi dan kecernaan serat kasar serta lemak kasar. Hasil analisis sidik ragam ANOVAberpengaruh tidak nyata (P>0,05) terhadap konsumi dan kecernaan serat kasar serta lemak kasar.Dapat disimpulkan bahwa penggunaan campuran tepung daun kelor dan tepung daun katuk hinggalevel 15% dalam ransum memberikan pengaruh yang sama terhadap konsumsi dan kecernaan seratkasar serta lemak kasar pada ternak babi fase grower.